THE ADDED VALUE OF SMOKE CATFISH ( Pangasius sutchi ) ( CASES CATFISH PROCESSING IN KOTO MASJID VILLAGE XIII KOTO KAMPAR DISTRICT RIAU PROVINCE) - Yonda Defrianti Putri; Lamun Bathara; Hendrik ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Research on Added value of smoke catfish ( Pangasius sutchi ) ( Cases Catfish Processing in Koto Masjid Village XIII Koto Kampar District Riau Province) should be conducted in march 2016 in Koto Masjid village the kabupaten kampar Riau Province. This study attempts to ( 1 ) to know much value added economical catfish after processed into catfish smoke , ( 2 ) know the production and marketing catfish smoke. Methods used is the method case study such respondents in purposive sampling as many as 3 people who have a role as processing catfish smoke. Based on the results of research ( 1 ) added value of smoke catfish is Rp.3.265,6 per kilogram fresh catfish by a ratio of added value of Rp. 18,1422 .The advantage gained catfish processing smoke is Rp. 2.465,6 per Kilogram with operating margin Rp. 3.700 per Kilogram catfish fresh ( 2 ) in once used of fish production catfish fresh with 1.000 Kg , produce 300 kg of smoke catfish .Of processing of smoke catfish is still in traditional. Smoke Catfish produce tea processing factory in the village Koto Masjid was marketed in pekanbaru 20 %, to palembang as many as 5 % , to malaysia as many as 5 %, to the market Air Tiris 15 % , market kuok 15 % , Bangkinang market as many as 12 % , Kampar market as much as 13 % and in taratak Buluh 15 % . Keywords: Added value, Smoke Catfish , Processing , Koto Masjid